The life cycle of a metropolitan business network: Liverpool 1750–1810 - Haggerty, John; Haggerty, Sheryllynne (Explorations in Economic History, 2011)
Recently historians have complicated their understanding of networks. In particular, they have started to assess the role of networks in civic and formal arenas. This paper posits a quantitative methodology for a more nuanced and sophisticated analysis of mercantile networks within this environment. It uses visual analytics of Liverpool's business networks comprising political, trade, social and cultural institutions to assess their role in the changing social and economic climate during the period 1750–1810. This paper demonstrates the dynamic role of networks in the shaping of a metropolitan economy and the interplay between the two. In addition, it posits that, as is the case for regional clusters, there is a life cycle of networks. In this way, we are able to see how the networks sustained, nurtured and transformed social and economic activity during this period.
Keywords: Liverpool; Merchants; Metropolitan business networks; Trade; Visual analytics